PERAN BUKIT DOA DALAM PENINGKATAN KESEJAHTERAAN MENTAL: STUDI KASUS DI PANCUR BATU - Amanda Husnatul Nazli; Wan Yara Yasmin; Dita Wahyuni; Rani Suraya (CV. ADIBA ADISHA AMIRA, 2025)
This study aims to explore the role of Bukit Doa in Pancur Batu in helping drug users, drug dealers, and people with mental disorders (ODGJ) restore their mental well-being. Using a qualitative approach and case study method, data were collected through direct observation and in-depth interviews with two informants, namely the Program Manager and the Counselor of the Companion Revision. The results of the study indicate that the rehabilitation program at Bukit Doa integrates medical, social, and spiritual approaches, which include counseling, community therapy, and religious support. The main challenges include participant resistance, limited facilities, community stigma, and limited funds, which are overcome through a personal approach, community education, and cross-subsidies. The impact of the program is seen from changes in participant behavior, increased community awareness of the dangers of drugs, and re-acceptance of participants in the social environment. Although independent funding is an obstacle, the program shows sustainability through organized management. This study highlights the importance of synergy between medical and spiritual approaches in community- based rehabilitation to address mental health and drug problems holistically.